HIV continuum of care among trans women and travestis living in São Paulo, Brazil - Rocha, Aline Borges Moreira da; Barros, Cláudia; Generoso, Igor Prado; Bastos, Francisco I.; Veras, Maria Amélia (Revista de Saúde Pública, 2020)
OBJECTIVE: To examine the HIV care cascade among trans women and travestis in São Paulo – Brazil, the most populous city in South America. METHODS: Using data from a cross-sectional study carried out between November 2016 and May 2017 in the city of São Paulo (Divas Research). Respondent driven sampling (RDS) was used to recruit 386 transgender women and travestis who participated in a HIV risk survey and were tested for HIV. The cascade was defined as HIV prevalence, HIV diagnosed, Antiretroviral (ART) Prescription, and currently on ART. A multiple analysis model was conducted to identify the association between sociodemographics and the cascade gaps. RESULTS: Of the trans women living with HIV, 80.9% were already diagnosed, 76.6% of them had been prescribed, of which 90.3% were currently on treatment. Those who were registered in care had a higher rate of ART (aPR 2.06; 95%CI 1.09-3.88). Trans women between 31-40 years old (aPR 1.65; 95%CI 1.09-2.50) and those older than 40 (aPR 1.59; 95%CI 1.04-2.43) had higher prevalence of ART. CONCLUSIONS: Our data suggest an increase in the testing and treatment policy implementation among trans women in the city of São Paulo, although gaps have been found in the linkage to care. However, young trans women and those not registered in health care service may benefit from efforts to engage this part of the population in care to improve HIV treatment and care outcomes.